Replacing print with e-journals: can it be done - a case study - Bevan, Simon J.; Nieminen, Satu; Hunn, Ruth A.; Sweet, Michelle (United Kingdom Serials Group, 2003)
This article describes the introduction and management of e-journals at Cranfield University and considers the training and education issues related to this implementation
Keywords: Cranfield Library Service; electronic journals